Kwanŭm (Avalokiteśvara) Divination: Buddhist Reconciliation with Confucianism in the Late Chosŏn - Seong U. K. Kim (Religions, 2020)
This paper looks at the interactions between Buddhism and Confucianism in the late Chosŏn era through a case study of Kwanŭm (Avalokiteśvara) divination and, thereby, attempts to demonstrate how Buddhist monks navigated their religion in a Confucian-dominant society. In particular, it discusses how Chosŏn Buddhist monks incorporated Confucian ethical values into the practice of Avalokiteśvara divination, which developed in the late Chosŏn era, based on the Kwanŭm yŏnggwa, the first Korean Buddhist manual for Avalokiteśvara divination. The unique amalgam of the Avalokiteśvara cult and divination practices became popular in this period by embracing the fulfillment of the Confucian duty of filial piety and sincerity as its essential element. In particular, the Confucian practice served as a deciding factor to receive the bodhisattva’s blessings in this divination. The introduction of Avalokiteśvara divination, therefore, reveals another strategy of the Buddhist community to demonstrate its devotion by incorporating the ideology of the Confucian ruling class in the late Chosŏn era.